2007
DOI: 10.1080/01926180600814601
|View full text |Cite
|
Sign up to set email alerts
|

Identity Development, Differentiation, Personal Authority, and Degree of Religiosity as Predictors of Interfaith Marital Satisfaction

Abstract: This study investigated four predictors of interfaith marital satisfaction: identity status, differentiation, personal authority, and religiosity. A questionnaire was given to 84 interfaith married individuals assessing these four predictors plus marital satisfaction. Multiple regression analysis found that individuals with an achieved identity reported more marital satisfaction and individuals with a foreclosed identity reported less marital satisfaction. Differentiation also predicted increased marital satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…However, given the overlap between the concepts of differentiation of self and emerging adults’ core developmental tasks, it is possible that differentiation of self plays an important role in young people’s romantic experiences, and ultimately, their satisfaction in romantic relationships. Indeed, differentiation of self has been found to predict relationship satisfaction for married individuals (Parsons, Nalbone, Killmer, & Wetchler, 2007; Peleg, 2008). As dating relationships are common in emerging adulthood (Shulman & Connolly, 2013), the exploration of differentiation of self and its links with relationship satisfaction is warranted for this particular population.…”
Section: Differentiation Of Self In Emerging Adulthoodmentioning
confidence: 99%
“…However, given the overlap between the concepts of differentiation of self and emerging adults’ core developmental tasks, it is possible that differentiation of self plays an important role in young people’s romantic experiences, and ultimately, their satisfaction in romantic relationships. Indeed, differentiation of self has been found to predict relationship satisfaction for married individuals (Parsons, Nalbone, Killmer, & Wetchler, 2007; Peleg, 2008). As dating relationships are common in emerging adulthood (Shulman & Connolly, 2013), the exploration of differentiation of self and its links with relationship satisfaction is warranted for this particular population.…”
Section: Differentiation Of Self In Emerging Adulthoodmentioning
confidence: 99%
“…Higher levels of differentiation of self have been linked with better psychological adjustment in adulthood (e.g., Bray, Harvey & Williamson, 1987;Greene, Hamilton & Rolling, 1986;Jenkins, Buboltz, Schwartz & Johnson, 2005), greater capacity for emotional self-regulation, self regulation of attention and behavior, adult attachment security (e.g., Skowron & Dendy, 2004;Skowron, Holmes & Sabatelli, 2003;Thorberg & Lyvers, 2006;Wei, Vogel, Ku & Zakalik, 2005), and fewer psychological symptoms and relationship difficulties (e.g., Bartle-Haring, 1997;Bartle-Haring & Gregory 2003;Peleg, 2002;Schwartz, Thigpen & Montgomery, 2006;Skowron, 2000;Skowron & Friedlander, 1998;Skowron, Stanley & Shapiro, 2009). Studies have also shown that higher levels of differentiation of self are linked to greater marital satisfaction among heterosexual and same-sex couples (e.g., Kosek, 1998;Montes-Berges, 2009;Parsons, Nalbone, Killmer &Wetchler, 2007;Peleg, 2008;Skowron, 2000;Spencer & Brown, 2007), and adults who report greater differentiation of self are at lower risk for engaging in child abuse and other forms of family violence (Skowron, Kozlowski, & Pincus, 2010;Skowron & Platt, 2005). Also, findings indicate that differentiation appears to moderate (Knauth, Skowron & Escobar, 2006;Murdock & Gore, 2004) and mediate (Skowron Wester & Azen, 2004), the effects of stress on coping and adjustment in emerging adults.…”
Section: Introductionmentioning
confidence: 99%
“…Egy másik vizsgálatban feltárták, hogy a személyes autoritás csökkenti az elégedettséget a különbözõ felekezetû házasságokban (Parsons, Nalbone, Killmer, & Wetchler, 2007). Továbbá pozitív összefüggéseket találtak a PAFSQ összes alskálája és a marihuánafogyasztás között (Russo, 2009).…”
Section: A Személyes Autoritás a Családi Rendszerben Elméleteunclassified